A two-echelon location-routing model for designing recycling logistics networks with profit: MILP and heuristic approach. (1st June 2016) - Vidović, Milorad; Ratković, Branislava; Bjelić, Nenad; Popović, Dražen
Highlights: A 2E-LR problem for designing recycling network is presented. MILP model with profit and distance dependent collection rate. Efficient heuristics to solve large problem instances is developed. Abstract: This paper presents a mathematical formulation of a two-echelon location-routing problem in case of non-hazardous recyclables collection with a profit and distance dependent collection rate. The proposed model simultaneously determines collection points' locations respecting the dependency of collected recyclables' quantities on the distance between end users and collection points, the location of intermediate consolidation points (transfer stations) and routing of collection vehicles. For solving large problem instances, we have developed heuristics for obtaining good solutions in reasonable time. We tested our approach for different system parameters in order to get better insight into the system performance.